Harvest index and straw yield of five classes of wheat. (February 2016) - Dai, Jing; Bean, Brent; Brown, Bradford; Bruening, William; Edwards, Jeff; Flowers, Michael; Karow, Russell; Lee, Chad; Morgan, Gaylon; Ottman, Michael; Ransom, Joel; Wiersma, Jochum
Abstract: Wheat straw is a potential cellulosic feedstock for bioethanol. This study was conducted to evaluate straw yield potential and its relationship with grain yield for wheat ( Triticum spp.) grown in the United States. The specific objective was to determine if differences in straw yield and harvest index (HI) exist between and within regions and/or wheat classes. Using on-going variety performance trials in eight states, a total of 255 varietal trial entriess from five classes of wheat were surveyed for above-ground biomass. Averaged over all wheat classes and regions the HI was 0.45. Soft red winter wheat in Kentucky had, on average, the highest HI and lowest straw yield among regions and wheat classes. Soft white winter wheat under irrigation in the Pacific Northwest produced the highest straw yield. Hard red winter wheat in the southern plain states of Texas and Oklahoma had, on average, the lowest HI. Differences in the amount of precipitation and cultivars were the major contributors to the variation detected within wheat classes. The amount of wheat straw available as cellulosic feedstock in a state or wheat class can be estimated using the grain yield estimates provided by the National Agricultural Statistics Service and the class specific HI. Highlights: Harvest index was surveyed for 255 cultivars of five classes of wheat in eight states. Great variability in harvest index was detected within and between wheat classes. Harvest index ranged from 0.33 to 0.61 in the study. On average, soft red winter wheat had the highest harvest index and hard red winter wheat had the lowest.